The Impact of Socioeconomic Status on Elementary Student Achievement in Rural South Texas Schools - Martinez-Perez, Frances Ann; Kupczynski, Lori; Mundy, Marie-Anne (Advances in Social Sciences Research Journal, 2014)
The primary focus of the study is to analyze the effect of socioeconomic status on academic achievement by analyzing the scores of economically disadvantaged students in comparison to those of non-economically disadvantaged students on the State of Texas Academic Assessment of Readiness (STAAR) exam. Specifically, the study examines the 2013 STAAR reading and math scores of third, fourth, and fifth graders in attendance at four small rural schools in order to allow educators the capability to further understand the association between socioeconomic status and academic achievement among students in rural communities. Binary logistic regression is utilized and the results of analysis pointed out that socioeconomic status had a significant impact at the 4th grade level specifically. The results of this study provided information to be utilized by school leaders ranging from teachers all the way up to superintendents and on through higher education to inform teacher preparation curriculum that is specific to the needs of economically disadvantaged learners.